Determination of Adjustment Factors of Milk Yield According to Mature Age in Brown Swiss Breed Cattle - Kaygisiz, A; Şahin, O; Yilmaz, İ (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to determine adjustment factors for 305-day milk yield according to mature age in Brown Swiss cattle raised in Türkiye. A total of 19,042 milk yield records from 10,127 cows across 44 provinces were analyzed. Age correction factors were calculated using three methods: (i) Simple Averages Methods, (ii) Polynomial Regression Methods, and (iii) Gross Comparison Methods. The cows were divided into four calving seasons: spring, summer, fall, and winter. Results showed that cows calving in winter reached maturity at 37-39 months, earlier than those calving in other seasons. Adjustment factors for the youngest cows (≤ 24 months) and the oldest cows (≥ 109 months) were also determined to account for variations in milk yield. The study confirmed that winter-calving cows exhibit higher early lactation milk yields, likely due to favorable environmental conditions. These newly developed adjustment n factors provide a more precise estimation of genetic trends, aiding in more effective breeding strategies. Future studies with larger datasets are recommended to enhance accuracy further.